Exploratory Factor Analysis for Indonesian Version of PID-5 - Widhi Adhiatma; Rebeka Pinaima; Lusiana Bintang Siregar; Prischa Nova; Khristina Kencana; Magdalena S. Halim; Benedicta P. Dwi Riyanti (ANIMA Indonesian Psychological Journal, 2014)
Personality Inventory for DSM-5 (PID-5) is an instrument aimed for measuring pathological personality trait based on DSM-5’s Personality Disorders model which contains five pathological personality domains and divided into 25 pathological personality facets. The form of this instrument is a self-report consisting 220 items. The development of Indonesian Version of PID-5 is considered important because the existence of this instrument will assist the clinicians to identify the personality disorders based on DSM-5. This study performs the exploratory factor analysis (EFA) technique for all PID-5 facets to test the construct validity and to acknowledge the structure of factor in this Indonesian version of PID-5. This test was carried out by involving samples from 245 normal individual population (male = 88, female = 157) with an average of 23.31 years old. The result of EFA test showed that the amount of factors generated by the Indonesian version of PID-5 facets were six factors, which differs from the amount of factors generated by the original version of PID-5. This finding has similarities with other studies about personality instruments using the basic theory of Big-5 in Asia.